2007
DOI: 10.1103/physreve.76.042103
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated movement of inertial Brownian motors driven by a load under an asymmetric potential

Abstract: Based on recent work [L. Machura, M. Kostur, P. Talkner, J. Luczka, and P. Hanggi, Phys. Rev. Lett. 98, 040601 (2007)], we extend the study of inertial Brownian motors to the case of an asymmetric potential. It is found that some transport phenomena appear in the presence of an asymmetric potential. Within tailored parameter regimes, there exists two optimal values of the load at which the mean velocity takes its maximum, which means that a load can facilitate the transport in the two parameter regimes. In add… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…In the one-dimensional symmetric periodic system, the interplay between the ac driving force and the thermal equilibrium fluctuations can induce absolute negative mobility [15]. In the same system, multiple current reversals were observed in an asymmetrical potential [16]. Hänggi and coworkers [17] found that asymmetry in shape can cause absolute negative mobility.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the one-dimensional symmetric periodic system, the interplay between the ac driving force and the thermal equilibrium fluctuations can induce absolute negative mobility [15]. In the same system, multiple current reversals were observed in an asymmetrical potential [16]. Hänggi and coworkers [17] found that asymmetry in shape can cause absolute negative mobility.…”
Section: Introductionmentioning
confidence: 96%
“…The absolute negative mobility in the ratchet systems has received much attention [14][15][16][17][18][19][20]. Eichhorn and coworkers [14] considered a single Brownian particle in a spatially symmetric, periodic system far from thermal equilibrium and found that the average particle velocity is negative for positive force and positive for negative force.…”
Section: Introductionmentioning
confidence: 98%
“…In Ref. [17], Ai and Liu extended the study of inertial Brownian motors to the case of an asymmetric periodic potential. They found that a load can facilitate the transport and multiple current reversals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the transport of inertial Brownian motors in ratchet potentials driven by noise has been studied only in few works [14][15][16][17], which considered the mass of the particle. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…There are two central topics as to the studies of Brownian motors: one is the velocity properties of the transport of the Brownian particles [36][37][38][39][40][41]; and another is the thermodynamic properties [13,14,20,35,42], i.e., the mechanism and efficiency of energy conversion of the Brownian motor. Derényi et al [43] gave a definition of generalized efficiency of the microscopic engines and analyzed its application to a Brownian heat engine.…”
Section: Introductionmentioning
confidence: 99%